Blood urea nitrogen as a predictor of mortality in myocardial infarction (Universa Medicina, 2013)
INTRODUCTIONBlood urea nitrogen and creatinine levels are routine laboratory tests for evaluating renal function. Renal dysfunction has been related to worse prognosis of cardiovascular diseases. The purpose of this study was to determine the relationship between admission blood urea nitrogen and creatinine levels with in-hospital mortality in acute myocardial infarction patients. METHODSA cross-sectional study was performed using secondary data of 80 acute myocardial infarction patients hospitalized in Intensive Cardiac Care Unit of dr. Wahidin Sudirohusodo Hospital, Makassar, from June 2010 to July 2011. Admission blood urea nitrogen and creatinine levels were analyzed with Mann Whitney and Chi-Square tests.RESULTSMortality risk in the patients with blood urea nitrogen levels >50 mg/dL was 3.58 higher compared with those with blood urea nitrogen levels 1.1 mg/dL was 3.0-fold higher compared to patients with creatinine levels